Investigating the relationship between cash assets, sensitivity of investment flows and financing costs of listed companies in Tehran Stock Exchange - Salehnezhad, Seyed Hasan (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2016)
Link to publisher's homepage at http://ijbt.unimap.edu.my